PROJECT MANAGEMENT FOR THE DESIGN PROFESSIONAL : A Handbook for Architects, Engineers, and Interior Designers - Burstein, David, 1947- 365522, author; Stasiowski, Frank, 1948- 461925, author (New York : WHITNEY LIBRARY OF DESIGN, 1991)
Includes bibliographical references (pages 170-171) and index.